Palestinian Health Care Workers' Stress and Stressors During COVID-19 Pandemic: A Cross-Sectional Study - Beesan Maraqa; Zaher Nazzal; Therese Zink (SAGE Publishing, 2020)
Background: COVID-19 is thought to be the most significant public health threat the modern world has encountered. Health care workers (HCWs) face enormous pressure due to work overload, negative emotions, exhaustion, lack of contact with their families, and risk of catching the infection and death. Aim: This study aims to assess the level of stress perceived by HCWs and possible associated factors during the COVID-19 outbreak in Palestine. Methods: A cross-sectional sample of 430 frontlines HCWs was conducted using an online self-reported questionnaire. HCWs' stress from the COVID-19 outbreak, factors that increase stress, and the activities that reduced stress were assessed. Chi-square test was used to compare between a categorical variable and the study outcome; associations are presented as odds ratios (OR) and confidence intervals (95% CI) with 0.05 significance level. Al-Najah National University institutional review board granted ethics approval. Results: Most respondents (74.0%) reported high-stress levels during the outbreak. Fear of transmitting the virus to family was the most stressful factor (91.6%). HCWs who did not have training on the outbreak response were more likely to have high-stress levels (OR = 2.7 [95% CI = 1.7-4.4], P  < .001). Those with high stress reported being disappointed (OR = 2.4 [95% CI = 1.5-3.6], P  < .001), and strongly considered taking sick leave (OR = 3.9 [95% CI = 1.9-7.9], P  < .001). Conclusion: HCWs are under tremendous stress, given the ongoing COVID-19 pandemic. Understanding the psychological impact of the outbreak on HCWs and the activities that mitigate the stress is crucial to guide policies and interventions that can maintain psychological well-being.